Social Resilience : Earthquake Consequences to an Intense - Meza, Anicia Katherine Tarazona; Chavez, Sandra Auxiliadora Romero; CedeÃƒÂ±o, Elizabeth Alejandra EspÃƒÂn (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2017)
Disclosed generally the impact they have caused to the life of society intense seismic activity in the area, especially the tectonic situation of Ecuador and particularized on stage at the coastal territory, given its proximity to the Ring of Fire. a balance of the most intense earthquakes occurred during the twentieth century and in the time of this century and is particularized in the consequences resulting therefrom for society is shown. An analysis related to the vision deployed by the UN related to resilience as a capacity to prevent disasters and crises are addressed, as well as to foresee natural disasters, minimize them, take them into account or recover from them on time and in an efficient and sustainable including protection. The results of an assessment of the resilience evacuees at Camp âLos Tamarindosâ Portoviejo city where the SV-RES scale methodology that evaluates twelve dimensions developed offered.